HUBUNGAN JOB INSECURITY DAN BEBAN KERJA MENTAL DENGAN STRES KERJA PERAWAT HONORER DI RSJD ATMA HUSADA MAKAHAM SAMARINDA - Retno Wulandari (Universitas Widya Gama Mahakam Samarinda, 2017)
Stress is a dynamic condition of an individual faced with opportunities, limitations, or demands in accordance with expectations and results to be achieved in important and uncertain conditions. According to the National Institute for Occupational Safety and Health (NIOSH), nurses are professions that are very high risk of stress. Results of a survey by the Persatuan Perawat Nasional Indonesia (PPNI), where in 2006, approximately 50.9% of hospital nurses working in four provinces experienced work stress. This study aims to determine the relationship of job insecurity and mental workload with job stress contract nurses at RSJD Atma Husada Mahakam Samarinda. This research uses analytic survey method with cross sectional research design. The variables in this study are Job Insecurity, Mental Workload and Job Stress. The respondents of this research are contract nurses at RSJD Atma Husada Mahakam with total subject of this research is 74 respondents, sampling technique using Total Sampling. Data were analyzed by using Pearson Correlation test with ? = 0,05. The result showed that there was a relationship between job insecurity (p = 0.0001) and mental workload (p = 0,004) with work stress. The conclusion of this research is job insecurity and mental work load is the factor causing the occurrence of job stress on contract nurses at RSJD Atma Husada Mahakam. It is advisable to pay more attention to the nurse's need to reduce the level of job insecurity and mental workload by raising nurse staffing status for nurses with more than 5 years working period and providing pension guarantee and providing training to improve nurse's ability.